2015
DOI: 10.4172/2157-7471.1000314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spacing in Incidence and Severity of Garlic Rust (Puccinia Allii (Rudolphi.) and Bulb Yield and Related Traits of Garlic at Eastern Ethiopia

Abstract: Garlic rust is caused by Puccinia allii (Rudolphi) extremely hinder the productivity of Alliaceae species, especially garlic (Allium sativum). The disease has been found wherever garlics are cultivated and at present no system of control has been found that fully prevents the occurrence of the disease. A field experiment was conducted to determine the optimum planting density for abating garlic rust in order to maximize yield of garlic. The experiment was laid out in RCBD with three replications, garlic local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…Reduced plant population density could be one tool in a program to manage Ascochyta blight of faba bean. Decreasing disease severity level of faba bean observed with 100 kg ha -1 seed rate could be due to proper aeration resulting in decreased humidity level suitable for fungus growth and decreasing plant population also limits the transmission of rust pathogen to the next plant as confirmed by Mengesha and Tesfaye, (2015). Disease incidence and severity tended to increase with increased plant spacing in susceptible cultivars as confirmed by Maasa et al (2006).…”
Section: Impact Of Row Spacing and Seeding Rate On Ascochyta Blight S...mentioning
confidence: 81%
“…Reduced plant population density could be one tool in a program to manage Ascochyta blight of faba bean. Decreasing disease severity level of faba bean observed with 100 kg ha -1 seed rate could be due to proper aeration resulting in decreased humidity level suitable for fungus growth and decreasing plant population also limits the transmission of rust pathogen to the next plant as confirmed by Mengesha and Tesfaye, (2015). Disease incidence and severity tended to increase with increased plant spacing in susceptible cultivars as confirmed by Maasa et al (2006).…”
Section: Impact Of Row Spacing and Seeding Rate On Ascochyta Blight S...mentioning
confidence: 81%
“…However, despite the lowest spacings between plants used (7.5 and 10 cm) for large clove-seeds resulted in a higher competition between the plants, lowering the total bulb weight, the high MBW in the spacing of 12.5 cm compensated the low plant population, resulting in a higher TBY and CBY. Moreover, no significantly higher MBW was found for the spacing of 15 cm; thus, the use of low plant densities results in low TBY and CBY (MENGESHA;TESFAYE, 2015;VIDYA, 2015).…”
Section: Resultsmentioning
confidence: 98%
“…Olfati, Najafabadi and Rabiee (2016) evaluated three spacings between rows (15, 25, and 35 cm) and found that the lowest spacing resulted in 78% higher TBY when compared to the highest. Mengesha and Tesfaye (2015) evaluated three spacings between plants (10, 15, and 20 cm) with 30 cm between rows and found 38% higher yield for the spacing of 20 cm (7.87 Mg ha -1 ), when compared to the spacing of 10 cm (4.85 Mg ha -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Reduced plant population density could be one tool in a program to manage Ascochyta blight of chickpea. Decreasing disease severity level of chickpea observed with 80 kg ha -1 seed rate could be due to proper aeration resulting in decreased humidity level suitable for fungus growth and decreasing plant population also limits the transmission of rust pathogen to the next plant as confirmed by Mengesha and Tesfaye, (2015). Higher plant density may lead to severe competition between plants and increase risk of disease and lodging of the crop, resulting in reduced grain yield as confirmed by Liaqat et al (2019).…”
Section: Impact Of Row Spacing and Seeding Rate On Ascochyta Blight S...mentioning
confidence: 86%